Semelhança de alimentos funcionais e biomateriais com relação à tolerância imunológica - França, Eduardo Luiza; Pereira Júnior, Alfredo [UNESP]; Honório-França, Adenilda Cristina; Furlan, Fábio Augusto; Ferrari, Carlos Kusano (My University, 2010)
In spite of the differences of nature and use of functional foods and biomaterials, they share important similarities relatively to their interaction with the immune system. We describe major biochemical and physiological mechanisms of functional foods relatively to human health, and compare their action pathways with biomaterials. The main effects of functional foods comprise antioxidant activities, modulation of carcinogen detoxication enzymes, decreasing of aggregation of blood platelets, modifications of cholesterol metabolism and reduction of arterial blood pressure, steroid hormonal and endocrine control, antimicrobial activities, immunostimulant and antinflammatory activities. We suggest a similarity between these foods and the recent generation of biomaterials, relatively to their form of interaction with the immune system, opening the possibility of a synergic combination.

Apesar de suas diferentes naturezas e utilizações, os alimentos funcionais e os biomateriais apresentam importante semelhança no que tange a suas interações com o sistema imune. Neste ensaio teórico, descrevemos os principais mecanismos bioquímicos e efeitos fisiológicos dos alimentos funcionais relacionados à saúde humana, e comparamos sua forma de ação com a dos biomateriais. Os efeitos dos alimentos funcionais compreendem desde atividades antioxidantes, modulação de enzimas de detoxificação de agentes carcinogênicos, diminuição da agregação de plaquetas sanguíneas, alterações no metabolismo do colesterol e redução da pressão arterial, até o controle das concentrações de hormônios esteróides e do metabolismo endócrino, atividades antimicrobianas, atividades imunoestimulantes e antiinflamatórias. Sugerimos uma semelhança no modo de atuação destes alimentos e de nova geração de biomateriais na dependência de sua interação com o sistema imune, apontando para a possibilidade de uma utilização sinérgica.
Similarity of functional foods and biomaterials in regard to immunological tolerance
Keywords: Functional foods; Biomaterials; Immunology; Synergy; Tolerance; Biologia; Homeostase; Ontogenia; Sinais; Transdisciplinaridade